An analysis of factors that influence personal exposure to toluene and xylene in residents of Athens, Greece - Linos Athena; Chatzis Christos; Alexopoulos Evangelos C (BMC, 2006)
Abstract Background Personal exposure to pollutants is influenced by various outdoor and indoor sources. The aim of this study was to evaluate the exposure of Athens citizens to toluene and xylene, excluding exposure from active smoking. Methods Passive air samplers were used to monitor volunteers, their homes and various urban sites for one year, resulting in 2400 measurements of toluene and xylene levels. Since both indoor and outdoor pollution contribute significantly to human exposure, volunteers were chosen from occupational groups who spend a lot of time in the streets (traffic policemen, bus drivers and postmen), and from groups who spend more time indoors (teachers and students). Data on individual and house characteristics were obtained using a questionnaire completed at the beginning of the study; a time-location-activity diary was also completed daily by the volunteers in each of the six monitoring campaigns. Results Average personal toluene exposure varied over the six monitoring campaigns from 53 to 80 μg/m3. Urban and indoor concentrations ranged from 47 - 84 μg/m3 and 30 - 51 μg/m3, respectively. Average personal xylene exposure varied between 56 and 85 μg/m3 while urban and indoor concentrations ranged from 53 - 88 μg/m3 and 27 - 48 μg/m3, respectively. Urban pollution, indoor residential concentrations and personal exposures exhibited the same pattern of variation during the measurement periods. This variation among monitoring campaigns might largely be explained by differences in climate parameters, namely wind speed, humidity and amount of sunlight. Conclusion In Athens, Greece, the time spent outdoors in the city center during work or leisure makes a major contribution to exposure to toluene and xylene among non-smoking citizens. Indoor pollution and means of transportation contribute significantly to individual exposure levels. Other indoor residential characteristics such as recent painting and mode of heating used might also contribute significantly to individual levels. Groups who may be subject to higher exposures (e.g. those who spent more time outdoors because of occupational activities) need to be surveyed and protected against possible adverse health effects.